Implikasi Nilai-nilai Pendidikan Agama Islam pada Pagelaran Wayang Santri Ki Enthus Susmono dalam Keberagamaan Masyarakat Kabupaten Tegal - A.Alvian Fitrianto; Sulaeman Sulaeman; Herdianto Wahyu Pratomo (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2023)
The spread of Islam in Indonesia by WaliSanga is mostly done by utilizing the art/puppet show, because it is an art that is popular with the people so that it is easier to use to incorporate new teachings or values. It is precisely through puppet shows that Islamic values are introduced. Even the guardians often use other traditions or cultures in the community for the mission of preaching Islam because it is through the media that the values of Islamic teachings are easily conveyed and accepted by the community who at that time were still thick with their dynamism, animism, and beliefs that were far from Islam.In Tegal area there is a mastermind who is quite capable of Ki Enthus Susmono. Thanks to his skill and fame in the puppet world by being a puppeteer. Ki Enthus is one of the puppeteers who is able to bring the puppet show into a medium of communication and propaganda effectively. The name of wayang santri makes each performances convey Islamic religious messages.In wayang santri performances there are values of Islamic religious education including the value of aqidah, moral values, values of worship and social values, these values are in accordance with the teachings of Islam written in the Qur'an and Hadith of the Prophet Muhammad